The implementation of the Sistem Inovasi Cepat Penanganan ODGJ Terpadu (SICEPOT) in Sukabumi City - Ike Rachmawati; Dine Meigawati; Phan Doan Kieu Trang (Jurnal Pendidikan Vokasi, 2023)
As social beings, humans create dynamically changing situations and conditions. These conditions often require humans to adapt, but some people cannot cope with the demands of the times. To deal with People with Mental Disorders (ODGJ), the Sukabumi City government has developed the Sistem Inovasi Cepat Penanganan ODGJ Terpadu (SICEPOT). SICEPOT is an innovative health service system to minimize the growth in the number of mental disorders experienced by the people of Sukabumi City, especially in the Citamiang Sub-district area, West Java, Indonesia. Over the past three years, there has been an increase in ODGJ patients from 2019 to 2021, with information on 24 patients who did not seek treatment. One of the factors causing patients not to seek treatment is the need for more human resources to monitor ODGJ, especially at Tipar Health Centre in Sukabumi City. This study used qualitative research with a descriptive approach. Data collection techniques used were observation, interview, and documentation. Determination of informants was carried out using a proportional sampling technique on stakeholders that researchers in the study have determined. In implementing the SICEPOT program, researchers focused on 6 (six) implementation indicators, according to Mazmanian and Sabatier. The challenge in this innovation program is the need for more human resources to handle ODGJ patients. The consistency of Puskesmas Tipar has not been able to run well due to the postponement of the innovation program due to the COVID-19 outbreak. The involvement of policymakers and support from the community is one of the keys to implementing SICEPOT activities. Puskesmas Tipar uses technology for cross-sectoral coordination by using social media, namely WhatsApp.